2014
DOI: 10.1080/1747423x.2014.927011
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring land use/land cover change impacts on soils in data scarce environments: a case of south-central Ethiopia

Abstract: To monitor land-use/land-cover (LULC) change and assess its impact on the soil property, the availability of benchmark data is indispensable, which is hardly available in the intensively cultivated regions of developing countries. Our study attempts to solve this problem by generating a benchmark soil data through the development of modified spatial analogue (MSA) method in the context of the Upper Dijo River catchment, south-central Ethiopia. The magnitude and patterns of LULC changes were extracted from air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…LULCCs have been widely investigated in different parts of the world, e.g., in the USA and Europe [49], South America [44,50], Australia [51], Asia, and Africa [44], including Ethiopia [22,23,26,30,40]. These studies have shown that the expansion of agricultural land, both for commercial and subsistence crop production, is the main driver of LULCC [52].…”
Section: Major Drivers Of Lulcc/deforestationmentioning
confidence: 99%
See 1 more Smart Citation
“…LULCCs have been widely investigated in different parts of the world, e.g., in the USA and Europe [49], South America [44,50], Australia [51], Asia, and Africa [44], including Ethiopia [22,23,26,30,40]. These studies have shown that the expansion of agricultural land, both for commercial and subsistence crop production, is the main driver of LULCC [52].…”
Section: Major Drivers Of Lulcc/deforestationmentioning
confidence: 99%
“…Various authors addressed LULCC in Ethiopia, their focus varying greatly in terms of thematic area as well as spatial locations [20][21][22][23][24][25][26]. However, comprehensive and national scale analysis was conducted by the Woody Biomass Inventory and Strategic Planning Project (WBISPP), which has produced land use and land cover maps for Ethiopia [27].…”
Section: Yearmentioning
confidence: 99%
“…Preliminary field surveys before the present study also clearly indicated that gullies, landslides and riverbanks are the main sources of sediment in the catchment. As Ethiopia is characterized by a rugged topography, these problems remained critical challenges being aggravated by an increasing population pressure, lack of awareness and poor land management (Girma, 2001;Muys et al, 2006;de Mûelenaere et al, 2014;Mengistu & Waktola, 2014;Tesfaye et al, 2014;Ayele et al, 2015;Lanckriet et al, 2015;Mekonnen et al, 2015;Kassa et al, 2016;Mukai, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While, cultivated land and bare land jointly increased to Mengistu and Waktola (2014) showed that, that only 7.5% of the 1972 riverine trees were detected in 2004. About 92.5% of the riverine trees were converted into another LULC types.…”
Section: Land Use/land Cover Changes Between 1995 To 2015mentioning
confidence: 99%
“…Clay content, as opposed to silt and sand, varied significantly among LULC types. The LSD test showed significantly different clay content between soils of degraded lands and reference soils and finally resulted in change in soil texture (Mengistu and Waktola, 2014).…”
Section: Consequences Of Change In Lulcmentioning
confidence: 99%